Investigating radiatively driven, magnetized plasmas with a university scale pulsed-power generator - Halliday, JWD; Crilly, A; Chittenden, J; Mancini, RC; Merlini, S; Rose, S; Russell, DR; Suttle, LG; Valenzuela-Villaseca, V; Bland, SN; Lebedev, SV (AIP Publishing, 2022)
We present first results from a novel experimental platform that is able to access physics relevant to topics including indirect-drive magnetized inertial confinement fusion, laser energy deposition, various topics in atomic physics, and laboratory astrophysics (for example, the penetration of B-fields into high energy density plasmas). This platform uses the x rays from a wire array Z-pinch to irradiate a silicon target, producing an outflow of ablated plasma. The ablated plasma expands into ambient, dynamically significant B-fields (∼5 T), which are supported by the current flowing through the Z-pinch. The outflows have a well-defined (quasi-1D) morphology, enabling the study of fundamental processes typically only available in more complex, integrated schemes. Experiments were fielded on the MAGPIE pulsed-power generator (1.4 MA, 240 ns rise time). On this machine, a wire array Z-pinch produces an x-ray pulse carrying a total energy of ∼15 kJ over ∼30 ns. This equates to an average brightness temperature of around 10 eV on-target.